1993
DOI: 10.1002/hc.520040212
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical fragmentation of the 2‐phosphabicyclo[2.2.2]octa‐5,7‐diene ring system as a versatile method for generating 3‐coordinate methylene phosphine oxides and sulfides

Abstract: 1,6-Dihydrophosphinine I -oxides with 4-chloro-3(or 5)-methyl substituents give cycloadducts with dimethyl acetylenedicarboxylate having the 2-phospha-The fragmentation of bridged, strategically unsaturated heterocyclic systems is a powerful technique for the generation of small molecules with multiple bonding at the heteroatom. We have exploited this method in several ways to generate phosphorus species with multiple bonds. We have, for example, successfully generated the unsaturated, 3-coordinate fragment -P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Another way of utilizing the phosphabicyclooctene derivatives in phosphinylations is their UV light-mediated reaction with alcohols or amines [6][7][8][9][10]. Besides the eliminationaddition (EA) mechanism via a methylenephosphine oxide, a novel addition-elimination (AE) route involving an intermediate with a pentavalent pentacoordinated phosphorus atom was also substantiated by us [9,10,12,13].…”
mentioning
confidence: 84%
“…Another way of utilizing the phosphabicyclooctene derivatives in phosphinylations is their UV light-mediated reaction with alcohols or amines [6][7][8][9][10]. Besides the eliminationaddition (EA) mechanism via a methylenephosphine oxide, a novel addition-elimination (AE) route involving an intermediate with a pentavalent pentacoordinated phosphorus atom was also substantiated by us [9,10,12,13].…”
mentioning
confidence: 84%
“…It was found that the phosphabicyclooctadienes (1), because of their more strained framework, are more suitable for use in thermo induced fragmentations than the corresponding bicyclooctene derivatives (2) [6][7][8]. Both precursors (1 and 2), however proved to be excellent in UV-light mediated phosphorylations [2,4,5]. For the photolyses, we have substantiated an alternative mechanism involving an intermediate with a pentavalent, pentacoordinate phosphorus atom (4) furnishing the phosphorylated product (5) by fragmentation (Scheme 1) [2,9].…”
Section: Introductionmentioning
confidence: 94%
“…The bridged P-heterocycles (1 or 2) prepared by the Diels-Alder reaction of 1,2-dihydrophosphinine oxides with dienophiles [1][2][3] may undergo fragmentation to afford methylenephosphine oxide (3) that can be utilized in the phosphorylation of nucleophiles, such as hydroxy compounds and amines (Scheme 1) [2,[4][5][6]. It was found that the phosphabicyclooctadienes (1), because of their more strained framework, are more suitable for use in thermo induced fragmentations than the corresponding bicyclooctene derivatives (2) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The latter are novel phosphorylating agents toward a variety of nucleophiles, such as alcohols, phenols, and amines [1,2]. The reaction can be achieved either thermally [3], or under photochemical conditions [4][5][6]. In the latter instance, a novel addition-elimination mechanism was substantiated to be a competitive pathway [5][6][7] in addition to the traditional elimination-addition route involving methylenephosphine oxide as the intermediate [4].…”
Section: Introductionmentioning
confidence: 98%
“…The reaction can be achieved either thermally [3], or under photochemical conditions [4][5][6]. In the latter instance, a novel addition-elimination mechanism was substantiated to be a competitive pathway [5][6][7] in addition to the traditional elimination-addition route involving methylenephosphine oxide as the intermediate [4]. The fragmentation-related phosphorylations are of interest, as they require mild reaction conditions, especially those accomplished under photochemical conditions, (26 • C and an irradiation of only several hours) and take place efficiently and in a selective way [5,6,8].…”
Section: Introductionmentioning
confidence: 99%